Climate shocks, impacts, responses, and adaptive capacity of smallholder farmers (Webinar session 13) - Transforming Agrifood Systems in South Asia (TAFSSA) (International Maize and Wheat Improvement Center, 2024)
How are smallholders responding to climatic shocks in South Asia?: Need for an agrifood systems lens towards climate adaptation.